2020
DOI: 10.3390/ijms21238962
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA and Oxidative Stress in Influenza A Virus Pathogenesis

Abstract: MicroRNAs (miRNAs) are non-coding RNAs that regulate diverse cellular pathways by controlling gene expression. Increasing evidence has revealed their critical involvement in influenza A virus (IAV) pathogenesis. Host–IAV interactions induce different levels of oxidative stress (OS) by disrupting the balance between reactive oxygen species (ROS) and antioxidant factors. It is thought that miRNA may regulate the expression of ROS; conversely, ROS can induce or suppress miRNA expression during IAV infection. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…It was found that varied miRNAs were involved in the innate immune response upon IAV infection in humans [ 140 ]. On the one hand, some miRNAs play a positive role, inducing an antiviral immune response and inhibiting IAV replication.…”
Section: Influenza Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that varied miRNAs were involved in the innate immune response upon IAV infection in humans [ 140 ]. On the one hand, some miRNAs play a positive role, inducing an antiviral immune response and inhibiting IAV replication.…”
Section: Influenza Virusmentioning
confidence: 99%
“…miR-29c enhances the expression of A20 protein induced by IAV, inhibiting the activity of NF-κB and the expression of pro-inflammatory cytokines [ 144 ]. Previous reviews have well documented the multiple roles of miRNAs in the regulation of innate immunity upon IAV infection [ 140 , 145 ]. In addition to miRNAs, other noncoding RNAs such as long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs) may also involve regulation of mRNAs in control of gene transcription.…”
Section: Influenza Virusmentioning
confidence: 99%
“…Compared to RSV, influenza may increase leukotriene concentrations by inducing the 5-LOX pathway ( 103 ). Similar to RSV, the miRNA expression profile of host cells is significantly changed by influenza ( 111 ). Among these miRNAs, let-7, miR-21, and miR-29 have connections with AA metabolism and miR-29 activates COX-2 through epigenetic changes during influenza A infection ( 104 ).…”
Section: Linkages Between Mirnas and Leukotrienes During Other Respiratory Virus Infectionsmentioning
confidence: 99%
“…Abnormal expression of microRNAs (miRNAs) is associated with the pathogenesis and pathological process of various human diseases [7]. It is proved that miRNA levels have a major influence on DM and its complications including DR. For example, miR-18a-5p affects DR and inhibits retinal angiogenesis by targeting fibroblast growth factor 1 and hypoxia-inducible factor 1-alpha [8].…”
Section: Introductionmentioning
confidence: 99%